Diversity matters: opportunities in the study of the genetics of psychotic disorders in low- and middle-income countries in Latin America - Fonseca, Lais; Sena, Brena F.; Crossley, Nicolas; Lopez-Jaramillo, Carlos; Koenen, Karestan; Freimer, Nelson B.; Bressan, Rodrigo A.; Belangero, Sintia I.; Santoro, Marcos L.; Gadelha, Ary (Revista brasileira de psiquiatria, 2021)
Lack of diversity regarding genetic and environmental backgrounds weakens the generalization and clinical applicability of research findings on psychotic disorders. Notably, Latin Americans have been generally neglected in genetic studies, comprising less than 2% of genome-wide association study samples. But Latin American populations represent a unique opportunity for research, given the exceptionally high ethnic admixture of this group. Increasing genetic diversity is essential to improve the fine mapping of known regions associated with psychotic disorders, discover novel genetic associations, and replicate studies. Additionally, Latin America is characterized by massive social, political, and economic inequalities, all known risk factors for mental health issues, including psychotic disorders. This article aims to 1) discuss the challenges and advantages of studying Latin America's particular genetic makeup and environmental context; 2) review previous studies conducted in the region; and 3) describe three Latin American research initiatives in progress: the Neuropsychiatric Genetics of Psychosis in Mexican Populations (NeuroMEX), the Paisa, and the Latin American Network for the Study of Early Psychosis (ANDES) studies.